PNEI and youth sports activities: How food stress shapes the athlete`s body - Barsotti, N.; Bruscolotti, M.; Chiera, M. (EWF Scientific Magazine, 2019)
The management of an athlete`s diet, if ill-advised, can represent an excessive allostatic load and, if protracted over time, may determine a series of physical and psychological adaptations that can reduce the overall capacity of performance within the specific sport and on an even more serious note, affect the state of psycho-physical health of the athlete. This can lead to a deterioration in the ability to make technical-tactical choices, of the ability to adapt to the workload, exposing the athlete to a greater risk of injury. Precisely in consideration of the complexity of the PNEI network, it is advisable not to approach the phenomenon of an athlete`s nutrition in a reductionist way, also considering that due to the numerous interrelations between the variables involved, it is very difficult to identify specific allostatic load indices on which to intervene quickly and effectivelyfor the resolution of the problems we have seen can arise. For these reasons, it is essential to educate young athletes and their trainers on the basics of proper nutrition, including brief information programmes that fill the often highlighted gaps and to stress the importance of a diet based on foods capable of regulating the metabolism, the immune system and the intestine, and not on supplements often useless for the purpose of performance. especially in adolescent athletes.